(untitled) (El-Wahat Journal for Research and Studies, 2025)
One of the virtues of our Sharia is what it contains of tolerance and ease in all its rulings, and this is one of its noblest and greatest purposes that it looks to and aims to achieve. So what is the correct path that the seeker should take to observe the Sharia evidence in the light of the Sharia purposes, and what are the controls that he must take into account , in the hope of hitting what the wise legislator wants from his legislation ? And in the hope of knowing that, i made this research to explain something of that, especially since I allocated a side of it to one of the scholars of the nation - Ibn Bazaiza - in the applied side ,so that it would be model. The research came in the form of an introduction, a preface, three topics, and a conclusion. As for the introduction; It refers to something of the majesty of this science - I mean the science of purposes - and the conditions of people in it who looked at issues presented to them in its light.As for the topics; The first in defining Ibn Bazaiza and his book Rawdat al-Mustabin with some brevity, and the second in talking about the concept of moderation in the implementation of purposes, and the controls for achieving them, and the third in mentioning jurisprudential issues of Ibn Bazaiza - which I theorized before through his book Rawda al-Mustabin, and as for the conclusion; It contained the results obtained by the researcher; As a statement of the importance of the science of purposes in issuing judgments, to the extent that some of them made it a condition in the mujtahid, and such as the need to combine the word and the meaning and give each one his right of consideration and actions, so he is a mediator between those who prevail over one over the other, and among them is the danger of lack of moderation in the consideration of the purposes, which leads to falling into anomaly And perhaps even in heresy and atheism, and among them is the importance of the goal of balancing between benefits and evils, and that it is the comprehensive goal intended by the Sharia, and that it is a delicate and ramified chapter... Key Words: IBN,BAZIZA/RAWDAT,AL- MOSTABIN,controls,moderation/purposes